O trabalho profissional dos(as) assistentes sociais no INSS pós as contra-reformas da Previdência Social - Barbosa, Thalyta Mabel Nobre (2007)
The present research study the work professional of the Social worker in the National Institute of Social Security of Rio Grande do Norte s State, especially about the working terms, the demands and working process of Social worker in consequence of the limits established with disorganization of his institutional space derived of the Counter-Reforms of the State and of Social Security. In decade of 1990 there was in Brazil adhesion to the neoliberal politics what configured a new organization of work and a new performance of the State. Inside this context, it was accomplished the Counter-Reforms with emphasis in the privatizations, reform of the Social Security and of the device of the Brazilian State, among other actions. Particularly, in Social Service reforms brought profound consequences for the Social workers of INSS, among it: reduction of professionals and in his institutional space. This study situates the Social Worker of Social Security in front of the contemporary modifications in the world of work as well as in front of the consequences come upon of the Counter-Reforms implemented and executed by the neoliberal governments in the country of way the of frame and to enter to the globalized world and the new order of the capital. From the qualitative research based in the critical and dialectic theoreticianmethodological perspective that study the phenomena from your relations, mediations and contradictions, was possible unveil the limits and the possibilities of the professional work of the Social worker in INSS placed the Counter-Reforms of Social Security. Synthetically, the results of this investigation indicate that, there is an worsening in the inconsistency of the work with relation to social worker's functional situation and his working terms in the institution